Colonic Angiodysplasia with a Huge Submucosal Hematoma in the Sigmoid Colon - Takayuki Shimizu; Daisuke Koike; Yukihiro Nomura; Kenji Ooe (Case Reports in Surgery)
Colonic angiodysplasia (AD) with bleeding as a comorbidity in the aging population is being increasingly reported. However, to our knowledge, there is no report on colonic AD accompanied by a huge hematoma. Herein, we report a case of colonic AD with a huge submucosal hematoma. A 75-year-old man with sudden melena was referred to our hospital. Helical computed tomographic angiography (CTA) revealed bleeding from the sigmoid colon. Additionally, colonoscopy showed a huge submucosal hematoma with bleeding in the sigmoid colon. As endoscopic hemostasis was difficult, sigmoidectomy was performed. The pathological diagnosis was colonic AD. The present case indicates that colonic AD should be considered in the differential diagnosis for melena. In addition, the case shows that helical CTA, which is a noninvasive imaging modality, is useful for the diagnosis of colonic AD and is as effective as colonoscopy and angiography for diagnosis.